Opportunities and competition in thick labor markets: Evidence from plant closures - Peter Haller; Daniel F. Heuermann (Journal of Regional Science, 2019)
Since Marshall (1890), it has been widely held in urban economic theory that cities insure workers against the risk of unemployment by offering a larger pool of potential jobs. Using a large administrative panel data set on workers displaced as a result of plant closures, we examine whether positive effects from a higher urban job density are offset by more intense competition between workers. When controlling for the sorting of workers between regions, we find robust evidence that the effect of job competition on unemployment duration exceeds that of job opportunities in absolute value. Our results put the idea of urban risk-sharing into perspective and provide an explanation for observed longer unemployment durations in cities.
Keywords: 320; agglomeration; displacement; thick labor markets